Serum insulin-like growth factor-1 as a marker of improved liver function and surgical outcome in dogs with congenital extrahepatic portosystemic shunts. (August 2021) - Serrano, G.; Devriendt, N.; Paepe, D.; de Rooster, H.
Highlights: Serum IGF-1 concentration (sIGF-1c) increased post-shunt surgery in all dogs. Greater sIGF-1c increase in complete shunt closure than persistent shunting. sIGF-1c ratio had 93.7% sensitivity and 66.7% specificity to assess surgical outcome. sIGF-1c ratio was inferior to imaging modalities to assess surgical outcome. Abstract: Serum insulin-like growth factor-1 concentration (sIGF-1c) is reduced in various hepatopathies in humans and dogs. This work aimed to evaluate sIGF-1c in dogs before and after congenital extrahepatic portosystemic shunt (cEHPSS) attenuation, in relation to surgical outcome (closed vs. persistent shunting). Secondarily, it aimed to assess if sIGF-1c can discriminate between cEHPSS and portal vein hypoplasia (PVH) and finally compare sIGF-1c ratio (postoperative/preoperative sIGF-1c) to pre-prandial serum bile acids (preBA), post-prandial bile acids (postBA), bile acid stimulation test (BAST) and fasting ammonia (FA), regarding surgical outcome. Thirty-nine dogs were included: 15 with closed cEHPSS, 15 with persistent shunting and nine with PVH. Transplenic portal scintigraphy was used to classifiy surgical outcome. There was no significant difference in sIGF-1c between dogs with cEHPSS and those with PVH ( P > 0.05). Postoperative sIGF-1c increased in all dogs ( P < 0.001 and P = 0.023 for closed and persistent shunting, respectively) and the increase was more pronounced in closed cEHPSS than in persistent shunting ( P = 0.006). Using an optimal sIGF-1c ratio cut-off of 2.23, the sensitivity was 93.3% and the specificity was 66.7% for differentiation between surgical outcomes. Serum pre-prandial bile acids, postBA BAST and FA had sensitivities of 80%, 86.7%, 86.7%, 60%; and specificities of 100%, 93.3%, 93.3%, 100%, respectively. There was a greater increase in sIGF-1c after shunt closure than during persistent shunting; nevertheless sIGF-1c ratio was inferior to advanced imaging to assess surgical outcome.